2018
DOI: 10.1371/journal.pone.0192998
|View full text |Cite
|
Sign up to set email alerts
|

Profile of suicide attempts and risk factors among psychiatric patients: A case-control study

Abstract: BackgroundSuicidal behaviour remains challenging for clinicians to predict, with few established risk factors and warning signs among psychiatric patients.AimWe aimed to describe characteristics and identify risk factors for suicide attempts among patients with psychiatric disorders.MethodsMultivariable logistic regression analysis, adjusted for clinically important confounders, was employed to determine risk factors for suicide attempts within a psychiatric patient population.ResultsThe case (n = 146) and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
(42 reference statements)
3
21
3
2
Order By: Relevance
“…For example, Bhatt and colleagues found no association between depression and suicide attempts compared with the present study. However, their case group differed from the present study and included 3‐month as well as lifetime incidence . Likewise, Joe et al studied both 12‐month suicide attempts and lifetime suicide attempts in African American adolescents and found lifetime suicide attempts were related only with anxiety disorder; however, the psychiatric disorders associated with 12‐month suicide attempts in their study remained unclear.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…For example, Bhatt and colleagues found no association between depression and suicide attempts compared with the present study. However, their case group differed from the present study and included 3‐month as well as lifetime incidence . Likewise, Joe et al studied both 12‐month suicide attempts and lifetime suicide attempts in African American adolescents and found lifetime suicide attempts were related only with anxiety disorder; however, the psychiatric disorders associated with 12‐month suicide attempts in their study remained unclear.…”
Section: Discussioncontrasting
confidence: 59%
“…However, their case group differed from the present study and included 3-month as well as lifetime incidence. 30 Likewise, Joe et al 31 The same finding was true for impulsivity. This was also observed as a risk factor for suicide attempt, and a factor related to antisocial PD.…”
Section: Discussionmentioning
confidence: 81%
“…Our nding also corresponds with Ansell Emily B et al 16 where Borderline personality disorder was a signi cant predictor of any attempt in the presence of all personality disorders. Another study by Bhatt M et al 17 found that impulsivity and borderline personality symptoms were signi cantly associated with attempted suicide. This suggests that symptoms of impulsivity in personality are strong predictors of suicide and may act in many ways by impairing the ability to cope with any situation and by drawing a person into con icts with family members and others.…”
Section: Resultsmentioning
confidence: 97%
“…In our study suicide females who have attempted a suicide are more than males similar results were observed in other studies also. 8,9 Majority of subjects who have attempted suicide are in the age group 21 to 30. Which is in agreement with other studies as well where majority of suicide attempted individuals falls under age group 20 to 29 9 the number of suicide attempts were observed to be more in rural areas than in urban areas.…”
Section: Discussionmentioning
confidence: 99%